Análisis Estratégico de los Sistemas Socio-Ecológicos de Lagunas Costeras: Los Casos de Mar Menor (España) y Mar Chiquita (Argentina) - Renzi, Lucia; Veron, Eleonora; Barragán Muñoz, Juan Manuel (Costas, 2022)
The present work has realized an integrated analysis of the pressures that affect the state of ecosystems and their services, as well as of the management mechanisms car- ried out in two socio-ecological systems of coastal lagoons located in dissimilar geographical areas: the socio-ecolog- ical system of Mar Menor, Spain, and the socio-ecolog- ical system of Mar Chiquita, Buenos Aires, Argentina. To do this, each lagoon system has been considered as a socio-ecological system through the realization of the DPSIWR model. Even if socio-ecological systems present a different degree of conservation and of damage caused by the anthropic activities, the work has shown that the anthropic development around the lagoons is the same and that both the drainage basin and the maritime front present the same threats to the conservation of the coastal lagoons. For this reason, the managers and institutional entities involved in the environmental management should consider, not only the effects caused by the maritime front, but also the effects contributed by the activities carried out in the drainage basin of the coastal lagoons.